2012
DOI: 10.1016/j.acvd.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic prediction of postoperative atrial fibrillation after aortic valve replacement for aortic stenosis: A two-dimensional speckle tracking left ventricular longitudinal strain multicentre pilot study

Abstract: Incidence of POAF is high after AVR for severe aortic stenosis. Our results suggest an additive value of the study of left ventricular myocardial deformation to classical clinical and echocardiographic variables for the prediction of POAF in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…The influence of enlarged left atrial on POAF has been demonstrated with CABG in several studies [20]. However, other previous reports [2, 11, 21], abandon the correlation of the size of left atrium and AF, assuming that dysfunctional left atrial is distinct of atrial remodeling. That may atributed to the younger age of their population in comparison to ours.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of enlarged left atrial on POAF has been demonstrated with CABG in several studies [20]. However, other previous reports [2, 11, 21], abandon the correlation of the size of left atrium and AF, assuming that dysfunctional left atrial is distinct of atrial remodeling. That may atributed to the younger age of their population in comparison to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work using volumetric methods has demonstrated that the contractile phase of LA function is impaired following mitral valve repair, suggesting that pre-operative atrial dysfunction is masked by the presence of MR 33,34 . More recently, speckle-tracking techniques have been used to examine atrial function, and has subsequently proved useful in a number of clinical scenarios, including predicting the development of atrial fibrillation during cardiac surgery or in the presence of mitral valve disease 22,35,36 . Alterations in LA strain may reflect histopathological changes occurring within the atrium: in a group of patients who underwent LA biopsy at the time of surgery for MVP, the extent of fibrosis corresponded to reductions in atrial function derived using speckle-tracking imaging 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In asymptomatic moderate and severe AS patients with preserved LVEF, reduced GLS worse than -15% was a significant risk factor for cardiac hospitalization, AVR, cardiovascular death[30,31], all-cause mortality at one year[24], and, interestingly, increased risk of post-operative atrial fibrillation independent of left atrial size and age[32]. Other studies have established that regional deformation analysis is also important, with an additional parameter called basal longitudinal strain (BLS) less than -13% associated with adverse outcomes including heart failure, MI, all-cause mortality, and symptomatic status in asymptomatic severe AS.…”
Section: Aortic Stenosismentioning
confidence: 99%